SISTEM TATANIAGA CABAI MERAH KERITING DI KECAMATAN BANYUASIN III KABUPATEN BANYUASIN - Nasir, Nasir (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2021)
The aims are Knowing the marketing channel of curly red chili, Knowing the marketing function carried out by the curly red chili trading institution, Calculating trade system costs, trading margins, farmer's share and share in institutions involved in chili trading activities, Knowing the efficiency of the curly red chili trading system,  The research was carried out in Seterio Village, Banyuasin III District, Banyuasin Regency. The method used is a survey method for chili farmers and marketing institutions (chili traders). The data were analyzed using the formula for trading margins, trading costs, trading profits, farmer's share, institutional share and marketing channel efficiency. The results showed: the red curly chili trade system consists of 4 trading channels, namely: I = Farmers-collectors at village level-collectors at sub-district level-wholesalers- retailers-consumers, II=farmers-collectors at the sub-district level-wholesalers- retailers-  consumers, III = Farmers-collectors at village level-retailers-consumers,and IV = farmers-collectors at the sub-district level-retailers-consumers.  The marketing functions carried out in the chili trade system are: a) Exchange function: Buying and selling (performed throughout the institution), b) Physical function: transportation (performed by all trading institutions except wholesalers), c) Facility function: Standardization and grading (performed by sub-district traders and village collectors, wholesalers and retailers), risk assurance, financing and market information (performed by all trading institutions).  Chile trading margin value, namely: channel I = Rp. 3.350/kg, channel II= Rp. 4,200/kg, channel III = Rp. 4.197/kg and channel IV = Rp.3.350/kg.Farmer's share value in: channel I = 78.83%, channel II = 79.66%, channel III = 79.52% and channel IV = 83.29%. All of the curly red chili trades on various channels are efficient, and the most efficient is channel IV..